Synthesis of Pyridinecarbothionylaminopyridines and Conversion of Thioamide to Amide - Choi, S.K.; Yoon, J.W.; Lee, E.J.; Kim, J.S.; Kim, Y.Y.; Jung, D.I.; Hahn, J.T. (Asian Journal of Chemistry, 2011)
Pyridinecarbothionylaminopyridines as structural isomers were obtained by the reactions of 2,3-and 2-4-lutidine with aminopyridines and sulfur. Reaction of 2,6-lutidine with active methyl group anilines in the presence of sulfur gave the desired thioamides 5. Reaction of synthesized thioamides 5 with sulfur and SiO2 or SeO2 gave the corresponding amide 6. We now report conversion of thioamide to amide by using oxidizing inorganic reagent.